2022
DOI: 10.4103/ijo.ijo_1651_21
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile and outcome of ocular manifestation in Marfans syndrome in India

Abstract: Purpose: Marfan syndrome (MFS) is a genetic disorder associated with considerable morbidity and mortality. Presently, well-documented information on this condition is not available in India. Methods: In this retrospective cohort study, we recruited patients with clinically diagnosed MFS who presented to the outpatient department using revised Ghent nosology. We retrieved complete ophthalmic information, including vision, anterior and posterior segments,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Ectopia lentis is observed in 50% to 80% of Marfan syndrome cases, frequently presenting as the primary clinical manifestation [3].…”
Section: Discussionmentioning
confidence: 99%
“…Ectopia lentis is observed in 50% to 80% of Marfan syndrome cases, frequently presenting as the primary clinical manifestation [3].…”
Section: Discussionmentioning
confidence: 99%
“…Ectopia lentis is a hallmark ocular feature of MFS, which refers to the displacement or dislocation of the eye's natural lens from its normal position in the eye. Many studies have reported that myopia and ectopia lentis are the most prevalent ocular signs of MFS, observed in over 60% of the cases 21,22 . Other notable observations include early and severe myopia, retinal detachment, cataracts, glaucoma, flat cornea, and iris hypoplasia 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that myopia and ectopia lentis are the most prevalent ocular signs of MFS, observed in over 60% of the cases. 21,22 Other notable observations include early and severe myopia, retinal detachment, cataracts, glaucoma, flat cornea, and iris hypoplasia. 22 The high prevalence of ocular FBN1 is a large ECM protein that plays an important role in the formation and maintenance of elastic fibers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations